Analysis of the Impacts on the Psychological Changes of Chinese Returning College Students After the Outbreak of the 2019 Coronavirus Disease - Xue, Yingying; Pyong, Kwak Han; Oh, Sae Sook; Tao, Yingying; Liu, Taofeng (Frontiers in Public Health, 2022)
This work aims to analyze the impacts on the psychological changes of Chinese returning college students after the outbreak of the 2019 coronavirus disease (COVID-19). A questionnaire survey is used to take 1,482 college students who returned to school after the epidemic as the research objects. The Chinese college students' knowledge of the epidemic, alienation in physical education class, school happiness, and expectations for a healthy life in the future are investigated and analyzed. It is found that Chinese returning college students have relatively poor awareness of COVID-19, and the overall degree of alienation in physical education class is relatively low after the epidemic, with an average score of 3.55 ± 1.018. The overall level of school happiness is relatively high, with an average score of 4.94 ± 0.883; and the overall level of expectation for a healthy life in the future is relatively high, with an average score of 3.50 ± 0.840. It can be concluded that the epidemic has a great impact on the psychology of returning college students, and it is necessary to strengthen the mental health education of college students after COVID-19.